Glycosphingolipids of skeletal muscle: I. Subcellular distribution of neutral glycosphingolipids and gangliosides in rabbit skeletal muscle - Müthing, Johannes; Maurer, Ulrich; Neumann, Ulrich; Kniep, Bernhard; Weber-Schürholz, Sabine (Carbohydrate research, 1998)
Membrane vesicles were prepared from rabbit skeletal muscle, separated by sucrose density gradient centrifugation and characterized by their specific marker enzymes, ligand binding, and ion flux activities. The fractions obtained (in the order of increasing density) were sarcolemma (SL), T-tubules (TT), sarcoplasmic reticulum (SR1 and SR2) and triads/mitochondria (Tr/M). Their glycosphingolipid compositions were analyzed by biochemical and immunochemical methods with specific antibodies (TLC immunostaining) and characteristic patterns were obtained from respective membrane fractions, expressed on a protein basis. Glucosylceramide, the main neutral glycosphingolipid of rabbit muscle, was found in SL and TT fractions, whereas SR and Tr/M vesicles lack this compound. Lactosylceramide was selectively recovered in the SR1 fraction. G M3(Neu5Ac), the main ganglioside in rabbit muscle, was found to account for 64% in the SL, 13% in the TT, 7% in the SR1, 3% in the SR2 and 13% in the Tr/M fractions. IV 3Neu5Ac– nLcOse 4Cer was mostly abundant in SL and decreased in the order SL>TT, Tr/M>SR1, SR2. IV 6Neu5Ac– nLcOse 4Cer was only detected in the SL and Tr/M fractions in noteworthy quantities. Ganglio-series gangliosides G M1, G D1a, G D1b and G T1b displayed homogeneous distribution patterns in each membrane preparation. They were expressed only in small amounts but mainly in SL, TT and Tr/M vesicles and to less extent in SR1 and SR2 fractions. The presence of G M3(Neu5Ac) in the SL as well as on subcellular level was confirmed in transverse muscle cryosections by means of indirect immunofluorescence microscopy. The SL was brightly stained, but considerable intracellular fluorescence was observed as expected from the biochemical analyses. Thus, the neutral GSL and ganglioside expression of the SL and the intracellular membraneous network is different in skeletal muscle both in terms of quantitative and qualitative GSL composition as demonstrated in details by means of biochemical and immunochemical techniques. The modulatory functions of G M3 and gangliosides of the neolacto- and ganglio-series towards the voltage dependent Ca 2+-channel, largely preponderant in the triads-containing Tr/M fraction, is the subject of the accompanying paper (J. Müthing, U. Maurer, and S. Weber-Schürholz, Carbohydr. Res., 307 (1998) 147–157).